Training and Assistance in Digital Marketing Strategies for Managing SMEs Business at Melasti Beach in Ungasan Village - Eka Saputra, Upayana Wiguna; Reyes, Alma Pia Garcia; Riyasa, Ida Ayu Putri Widiasuari; Dewi, Nyoman Indah Kusuma; Wirga, I Wayan (Universitas Pendidikan Nasional, 2023)
The problem faced by the MSMES group (Local Culinary) is their inability to utilize digital media to promote the culinary culture of the community in Ungasan Village, Kuta Selatan Sub-district, and Badung Regency. The purpose of this activity is to provide social media training to the MSMES group (Local Culinary) to enable them to use digital media professionally. The expected benefits are that the MSMES group (Local Culinary) will be able to increase their product sales online and expand their market share. The methodology of this activity includes providing digital marketing training and giving an understanding of all the activities that can be done by the MSMES group (Local Culinary), from creating photo and video content with captions to making content calendars and using them. Advertising through social media and email to promote their business. The results of this activity are the creation of professional product image and video content, planned content calendars, and the use of advertisements to promote their products. This activity also benefits Politeknik Negeri Bali as the implementing institution by sharing knowledge with the wider community.